The Identification of a Tumor Infiltration CD8+ T-Cell Gene Signature That Can Potentially Improve the Prognosis and Prediction of Immunization Responses in Papillary Renal Cell Carcinoma - Wang, Jie; Huang, Meiying; Huang, Peng; Zhao, Jingjie; Tan, Junhua; Huang, Feifan; Ma, Ruiying; Xiao, Yu; Deng, Gao; Wei, Liuzhi; Wei, Qiuju; Wang, Zechen; et al. (Frontiers in Oncology, 2021)
Background CD8+ T cell, vital effectors pertaining to adaptive immunity, display close relationships to the immunization responses to kill tumor cell. Understanding the effect exerted by tumor infiltration CD8+ T cells in papillary renal cell carcinoma (papRCC) is critical for assessing the prognosis process and responses to immunization therapy in cases with this disease. Materials and Approaches The single cell transcriptome data of papRCC were used for screening CD8+ T cell-correlated differentially expressed genes to achieve following investigations. On that basis, a prognosis gene signature associated with tumor infiltration CD8+ T cell was built and verified with the cancer genome atlas data set. Risk scores were determined for papRCC cases and categorized as high- or low-risk groups. The prognosis significance for risk scores were assessed with multiple-variate Cox investigation and Kaplan-Meier survival curves. In addition, the possible capability exhibited by the cases’ genetic profiles to assess the response to immunization therapy was further explored. Results 621 cell death inhibiting RNA genes received the screen in single-cell RNA sequencing. A gene signature consisting of 7 genes (LYAR, YBX1, PNRC1, TCF25, MYL12B, MINOS1 and LINC01420) was then identified, and this collective was considered to be an independent prognosis indicator that could strongly assess overall survival in papRCC. In addition, the data allowed papRCC cases to fall to cohorts at high- and low-risk exhibiting a wide range of clinically related features as well as different CD8+ T-cell immunization infiltration and immunization therapy responses. Conclusions Our work provides a possible explanation for the limited response of current immunization checkpoint inhibiting elements for combating papRCC. Furthermore, the researchers built a novel genetic signature which was able to assess the prognosis and immunotherapeutic response of cases. These may also be considered as a promising therapeutic targets for the disease.